Preliminary Observations on Sal Mortality in Madhya Pradesh - Prasad, Ram; , Jamaluddin (Indian Forester, 1985)
The investigation and observations relating to sal mortality revealed a complex interaction between climatic parameters, physical soil attributes (soil compactness) converting the high forest into that of coppice origin and varied biotic factor. These factors have been responsible for the loss of plant cover and site deterioration resulting in the reduced tree vigour. The available data shows that insects and pathogens are not the primary factors responsible for all mortality. Their role is only secondary after the complex interactions of climatic, biotic and management factors have reduced the tree vigour. The causative factors could be summarised as has been given in a chart form (Fig 2).